Promotion and protection of the rights of Orang Asli in Peninsular Malaysia: a study of the Suhakam - Abdullah Khoso,; Yew, Vivien W.C. (School of Social, Development and Environmental Studies, Faculty of Social Sciences and Humanities, Universiti Kebangsaan Malaysia, 2015)
The Paris Principles resolution in the United Nations General Assembly are non-binding but considered highly important in guiding human rights practices in individual countries. In light of the Paris principles this study of the Human Rights Commission of Malaysia (Suhakam) focused on the extent of, and factors affecting its performance in promoting and protecting the rights of the community. The findings revealed Suhakam’s slow and less effective measures as the main reasons for the little protection of the rights of the Orang Asli . There were grey areas that Suhakam had not addressed effectively including representation of the Orang Asli within Suhakam and in other agencies, and discriminations on religious grounds and formal education. In conclusion, Suhakam would have to go beyond its ‘postman’ role to that of bringing real and desired change for the benefit of the Orang Asli.